Punctuation in Early Modern Texts: The English Translation of Rembert Dodoens’ Herbal in Handwriting and Printing - Lorente-Sánchez, Juan (Universidad de Valladolid, 2024)
The present paper analyses the punctuation of a handwritten and a printed version of a distinguished herbal from the Early Modern period—that is—the English translation of Rembert Dodoens’ A Niewe Herball or Historie of Plants. The paper aims to contribute to the dissemination of knowledge on the use and distribution of punctuation in Early Modern English texts of a diverse typology, as well as to provide fresh observations as regards the historical linguistic comparison between scribes and printers’ writing practices. All this considered, it pursues the following objectives: to undertake (i) a quantitative survey of the various punctuation marks occurring in the texts; (ii) a qualitative examination of these at macro- and micro-textual levels; and (iii) an evaluation of the similarities and differences between the manuscript and the printed versions.
La puntuación en textos del período moderno temprano: la traducción en inglés del herbario de Rembert Dodoens en la escritura a mano y en la impresión
The original publication is available at https://revistas.uva.es/index.php/esreview/en/index. DOI: https://doi.org/10.24197/ersjes.45.2024.60-92
Keywords: Lengua inglesa - Puntuación; Punctuation; Early Modern English; Herbal; Handwriting; Printing